1762 Introduction to learning theories and implications for classroom design. (1st October 2016) - Clement, M.
Abstract: Today's students may be underprepared for both graduate and undergraduate coursework, yet they seek to become professionals in their fields. Frustration on the part of all who teach in higher education has led to the question, "How do we teach today's students such that they master the content?" The answers to this question come from three areas: looking at traditional course design, backward by design, and transparent teaching. Additionally, the steps of lesson design and engagement techniques are important. Traditionally, professors planned a course by choosing a classic text, planning lectures, and hoping for the best. Traditional teaching can work, when the lessons are planned with visuals, informal assessments, and explicit teaching. Backward by design, also called understanding by design (Grant Wiggins and Jay McTighe's work), implies that an instructor look at the biggest, most important outcomes of a course, and then plan ways to get students to achieve those outcomes. Transparent teaching, as defined by Mary-Ann Winklemes, includes task, purpose, and criteria. Explicit explanations, crystal-clear aligned assessments, and a rationale of what is taught can improve student achievement. When much content must be mastered by students in order for them to progress to graduate school, or to begin their professional lives, explicit direct instruction can be powerful. Well-crafted, well-taught lessons achieve that end. Strategies for a single lesson include a focus, presentation of material, application/practice of material, and review/assessment. The knowledge base of learning continues to expand rapidly, and research-based methods of teaching do exist. The work of Brown, Roediger, and McDaniel has challenged traditional thought on how students learn, and influenced how professors can teach such that today's students can learn. All of these strategies can be used at all levels of teaching in animal science, to prepare the next generation of professionals in the field.